Surgery for colorectal cancer. Issue 1 (January 2020) - George, Jason; Rockall, Timothy
Abstract: Colorectal cancer surgery represents a major component of the colorectal service workload. A solid understanding of key anatomical and oncological principles is essential for safe practice. In this article we discuss these fundamental aspects of colorectal cancer surgery. The first part of the article will deal with preoperative staging, surgical planning and principles of oncological surgery. The second part will focus on some of the most common operations. We will describe key intra-operative principles involved in performing a right hemicolectomy, left hemicolectomy, anterior resection and abdomino-perineal resection. Laparoscopic colorectal cancer surgery is increasingly widespread and therefore our perspective will assume this approach by default. In the final section, we discuss the role of radiotherapy in rectal cancers, transanal surgery, resection of colorectal liver metastases and the rationale behind follow-up.